A unique DNA methylation signature defines a population of IFN‐γ/IL‐4 double‐positive T cells during helminth infection. Issue 6 (25th March 2014) - Deaton, Aimée M.; Cook, Peter C.; De Sousa, Dina; Phythian‐Adams, Alexander T.; Bird, Adrian; MacDonald, Andrew S.
<x xml:space="preserve">Abstract</x> Th1 and Th2 cell fates are traditionally viewed as mutually exclusive, but recent work suggests that these lineages may be more plastic than previously thought. When isolating splenic CD4+ T cells from mice infected with the parasitic helminth Schistosoma mansoni, we observed a defined population of IFN‐γ/IL‐4 double‐positive cells. These IFN‐γ+IL‐4+ cells showed differences in DNA methylation at the Ifng and Il4 loci when compared with IFN‐γ+IL‐4− (Th1) and IFN‐γ−IL‐4+ (Th2) cells, demonstrating that they represent a distinct effector cell population. IFN‐γ+IL‐4+ cells also displayed a discrete DNA methylation pattern at a CpG island within the body of the Gata3 gene, which encodes the master regulator of Th2 identity. DNA methylation at this region correlated with decreased Gata3 levels, suggesting a possible role in controlling Gata3 expression. These data provide important insight into the molecular mechanisms behind the co‐existence of Th1 and Th2 characteristics.